Potret Kekerasan dalam Rumah Tangga dalam Novel Bumi dan Lukanya karya Revianaaprl - Damayanti, Cici; Hayati, Yenni (Persona: Kajian Bahasa dan Sastra, 2024)
Research on domestic violence is a topic that must be known and studied. This studyaims to determine the forms of violence, factors causing violence, and the impact of violencein the novel Bumi dan Lukanya by Revianaaprl. This research is a qualitative research usingdescriptive method. The data collection techniques used in this research are reading andunderstanding the novel Bumi dan Lukanya by Revianaaprl, searching for and recordingevent characters related to the portrait of domestic violence in the novel Bumi dan Lukanyaby Revianaaprl, and inventorying data into the data inventory format related to the novelBumi dan Lukanya by Revianaaprl. The technique of analyzing data in this study is toidentify and classify data related to forms of violence, factors that cause violence, and theimpact of violence, interpret data, draw conclusions and write reports in accordance with thetheory of literary sociology. The results show that the forms of violence in the novel arepersonal violence and structural violence. The causal factors of violence found include:individual factors, social factors, cultural factors, environmental factors, and family historyfactors. The impact of domestic violence in the novel is divided into two, namely physicalimpact and psychological impact. The violence that emerges is a picture of the existing socialreality.